Mucin producing carcinomas of the breast. Cytological diagnostics - O. G. Grigoruk; T. A. Moskvina; L. M. Bazulina; E. S. Sigitova; A. S. Stepanova; V. K. Ilinskiy; T. V. Ponomarev; S. Yu. Bakharev (ABV-press, 2020)
The aim of the study is to estimate potentiality of the cytological diagnostics of different types of mucin producing carcinomas of the breast.Materials and methods. Cytological evidences of the investigation of 35 patients with mucinous mass in cytological specimens were studied. Different types of mucinous carcinomas which had been diagnosed by cytological method were identified retrospectively.Results. "Pure" mucous carcinomas were divided into two types: hypocellular (A) and hypercellular (B) (n = 9 (25.7 %) and 14 (40 %), respectively). Mixed carcinomas (mucous carcinoma with invasive no special type carcinoma) were noticed of 12 women (34.3 %). 24 cell characteristics of mucin producing carcinomas were identified. Some cytological characteristics were estimated due to multiple factor analysis and discriminant analysis.Conclusions. Investigation results indicated that cytological technique is a high-quality diagnostic method. The fraction of correct classification of mucous carcinoma types based on discriminant analysis was 92-99 %.The study protocol was approved by the biomedical ethics committee of The Altai State Medical University, Ministry of Health of Russia.